Zoraida and Carcayona - Lisette Balabarca-Fataccioli (Entangled Religions - Interdisciplinary Journal for the Study of Religious Contact and Transfer)
Studies on the representation of Muslim women in early modern Spanish literature are not numerous, and aspects of their religious identities and conversions are usually less examined. This paper focuses on the role of female Muslim characters in texts written between the sixteenth and early seventeenth centuries in Spain. In these works the female protagonists convert to a new faith: One to Islam, the other to Christianity. In doing so, they cut ties with the fatherly figure in order to follow the new religion. My research attempts to answer two questions: What does the paternal house represent in regards to the faith that the daughters are rejecting? What role does Islam play in the different approach to female characters’ faith?